Effect of mobile APP in the management and application of mineral and bone disorder in dialysis patients of chronic kidney disease - Gulimire Muhetaer; Yue Qu; Xiao-wen Ha; Ling Zhang; Xiao-yu Wang; Yong-wu Yu; Hong Jiang (Editorial Department of Journal of Clinical Nephrology, 2024)
Objective To explore the adjustment and impact of chronic kidney disease-mineral and bone disorder (CKD-MBD) parameters in maintenance dialysis patients utilizing the Doctor-Patient Care App (Renal Care App). Methods From August 2021 to March 2022, 102 maintenance dialysis (HD) and peritoneal dialysis (PD) patients were randomized into two groups of App management or control (n=51 each). Control group received standard treatment for CKD-MBD while App management group was treated with CKD-MBD management model facilitated by Renal Care App. Follow-up assessments occurred every 3 months over a 12-month period. Changes in serum calcium (Ca), serum phosphorus (P) and serum parathyroid hormone (iPTH) levels were recorded along with patient satisfaction and revisit rates. Results From August 2021 to March 2022, 102 maintenance dialysis (HD) and peritoneal dialysis (PD) patients were randomized into two groups of App management or control (n=51 each). Control group received standard treatment for CKD-MBD while App management group was treated with CKD-MBD management model facilitated by Renal Care App. Follow-up assessments occurred every 3 months over a 12-month period. Changes in serum calcium (Ca), serum phosphorus (P) and serum parathyroid hormone (iPTH) levels were recorded along with patient satisfaction and revisit rates. Conclusions Interventions utilizing the App management model prove advantageous in elevating the rate of CKD-MBD-related parameters attaining the standards among regular dialysis patients. This approach not only improves patient compliance and satisfaction but also demonstrates clinical significance for broader applications.